Factors Affecting the Action of Mothers to Massage in Infants at BPM Talitha - Rina Hanum; Mey Elisa Safitri (International Archives of Medical Sciences and Public Health, 2021)
Data from BPM Talitha that the number of mothers who have babies 0-12 months as many as 32 people. The number of babies born with low birth weight (LBW) has increased over the last 2 years. In 2014 the number of babies born with underweight was 7 people, while in the factors that influence mothers to massage their babies. This type of research is an analytic survey with a cross sectional approach. The research was conducted at BPM Talitha, Deli Serdang Regency. The total population is 32 people, and all of them are used as samples. Data were analyzed by univariate and bivariate using Chi- Square test. The results showed that the mother's knowledge was sufficient for 15 (46.9%) respondents, 18 (62.5%) negative attitudes, 20 (59.4%) respondents lacked support from health workers. The factors that influence mothers to massage their babies at BPM Talitha are knowledge (p = 0.005), attitude (p = 0.003), support from health workers (p = 0.004). It is hoped that health workers will provide health education about the benefits and advantages of doing baby massage to mothers at BPM Talitha so that mothers' knowledge and attitudes become more positive